Synthesis of 2-Mercaptobenzimidazole and Some of its Derivatives - Ahamed, Mohammed R; Narren, Shetha F; Sadiq, Amal S (Al-Nahrain Journal of Science, 2013)
The present work involved three steps: First step include synthesis of 2-mercaptobenzimidazole from reaction of o-phenylenediamine with carbon disulfide, in the second step: Alkylation of the 2-mercaptobenzimidazole with different alkyl halides or aryl to obtain thioether compounds. Third step: include oxidation of 2-mercaptobenzimidazole to disulfide, while oxidation of thioether compounds gave sulfone compounds by using hydrogen peroxide as oxidizing agent for (1-2h) with stirring at room temperature. The 2-mercaptobenzimidazole was prepared in autoclave. Structure confirmation of all prepared compounds were proved using FT-IR and elemental analysis (C.H.N.S) besides melting points.